Colour Space Based DCT Compression Algorithm on Acne Face Images (International Journal of Communication Systems and Network Technologies, 2018)
At some or the other time during their life Acne affects almost 85% of adolescents. Dermatologists use manual methods such as direct visual assessment but now a day they keep the patients details along with their photographs to assess the acne. It also provides helps in the mod-ern method of etreatment. The compression of such acne images needs to be done in order to save the storage space. Analysis of conventional compression method based on Discrete Cosine Trans-form (DCT) is done. The analysis of image compression for various quality factors (Q) is seen as variations in terms of Compression Ratio (CR), Peak Signal to Noise Ratio (PSNR) and Structural Similarity Index (SSIM). Also image representation can be done in various formats as RGB, YCbCr, and L*a*b* formats all of which have special applications. Here study is done to find that which format would give best results in terms of compromise between Q and CR. The objective of this research is to find a compression method that gives best results in terms of image quality indices (PSNR, CR and SSIM). The suitable quality factor for acne images is 50% for a block size of 8x8 as obtained from the results. The best image compression format for acne images is found to be L*a*b.
Keywords: DCT; YCbCr; Lab; SSIM